Comparison of Efficacy and Safety of Doxycycline + Rifampin Combination Versus Rifampin + Trimethoprim-Sulfamethoxazole Combination in the Treatment of Brucellosis - Ayşe ERBAY (Flora Infeksiyon Hastalıkları ve Klinik Mikrobiyoloji Dergisi, 2002)
Brucellosis is a zoonosis existing worldwide. Although a variety of combinations of drugs have been used in the treatment of brucellosis, the best regimen has not been clearly determined. In our study 50 cases of acute brucellosis were examined prospectively to compare the efficacy of doxycycline plus rifampin versus rifampin plus trimethoprim-sulfamethoxazole combinations. No statistically significant difference was found between the two regimens but early clinical response was observed in rifampin plus trimethoprim sulfamethoxazole combination.